Fabrication of DNA microarrays on polydopamine-modified gold thin films for SPR imaging measurements - Wood, Jennifer B (Langmuir : the ACS journal of surfaces and colloids, 2013)
Polydopamine (PDA) films were fabricated on thin film gold substrates in a single-step polymerization-deposition process from dopamine solutions and then employed in the construction of robust DNA microarrays for the ultrasensitive detection of biomolecules with nanoparticle-enhanced surface plasmon resonance (SPR) imaging. PDA multilayers with thicknesses varying from 1 to 5 nm were characterized with a combination of scanning angle SPR and AFM experiments, and 1.3 ± 0.2 nm PDA multilayers were chosen as an optimal thickness for the SPR imaging measurements. DNA microarrays were then fabricated by the reaction of amine-functionalized single-stranded DNA (ssDNA) oligonucleotides with PDA-modified gold thin film microarray elements, and were subsequently employed in SPR imaging measurements of DNA hybridization adsorption and protein-DNA binding. Concurrent control experiments with non-complementary ssDNA sequences demonstrated that the adhesive PDA multilayer was also able to provide good resistance to the nonspecific binding of biomolecules. Finally, a series of SPR imaging measurements of the hybridization adsorption of DNA-modified gold nanoparticles onto mixed sequence DNA microarrays were used to confirm that the use of PDA multilayer films is a simple, rapid, and versatile method for fabricating DNA microarrays for ultrasensitive nanoparticle-enhanced SPR imaging biosensing